The Influence of Good Corporate Governance, Social Capital, and Organizational Culture on the Financial Performance of Village Credit Institutions in Bali - Susila, I Nyoman Dharma; Setijaningsih, Herlin Tundjung (E-Jurnal Akuntansi, 2025)
This study examines the influence of Good Corporate Governance (GCG), social capital, and organizational culture on the financial performance of Village Credit Institutions (LPDs) in Bali. Data were collected from 100 LPDs selected using proportional sampling and analyzed using Structural Equation Modeling (SEM) with Partial Least Square (PLS). The findings reveal that GCG, social capital, and organizational culture significantly and positively affect financial performance. Effective GCG enhances stakeholder trust, social capital fosters collaboration with local communities, and strong organizational culture improves operational efficiency. The study concludes that integrating GCG, social capital, and organizational culture is crucial for ensuring the sustainability and competitiveness of LPDs. Practical implications include the need for training, supportive regulations, and strategies aligned with local wisdom, such as Tri Hita Karana. Keywords: Good Corporate Governance; Social Capital; Organizational Culture; Financial Performance; LPD.